Inter treadmill variation in belt velocity regulation - Willwacher, S.; Oberländer, K. D.; Mai, P.; Mählich, D.; Kurz, M.; Koopmann, T.; Fohrmann, D.; Kantarev, A. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of the present study was to develop a novel method to quantify instantaneous belt velocity and to investigate differences in belt velocity regulation between different types of treadmills. We used circular cut-outs of reflective tape attached to the lateral aspects of the treadmill to determine its instantaneous belt velocity. By testing three treadmills with seven participants we were able to identify clearly different instantaneous belt velocity patterns between treadmills. Peak deviation amplitudes correlated positively with the body mass of runners, even though the slope of this relationship was different between treadmills for positive deviations from target speed. These results highlight the importance of considering belt velocity regulation differences in human locomotion studies and treadmill training.